2016
DOI: 10.1245/s10434-016-5631-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Local and Distant Recurrence Patterns in Patients with Triple-Negative Breast Cancer According to Age

Abstract: Background Triple-negative subtype (TNBC) and young patient age are both associated with an increased risk of local recurrence (LR) and distant recurrence (DR). In young women with TNBC, it is unclear whether subtype or patient age is driving prognosis. Methods Patients treated for primary TNBC from 1998 to 2011 were identified from the breast surgery database. Clinico-pathological characteristics, treatment, and outcomes were compared between patients < 40 and ≥ 40 years of age at diagnosis. Multivariate mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 31 publications
0
27
1
1
Order By: Relevance
“…Radosa et al. retrospectively reported that younger patients were more likely to present with a higher stage of disease; however, younger age was not an independent risk factor for local recurrence in patients with TNBC [35] . Therefore, age may not be a crucial factor for LRR among patients who presented at a similar clinical stage and all received chemotherapy.…”
Section: Discussionmentioning
confidence: 97%
“…Radosa et al. retrospectively reported that younger patients were more likely to present with a higher stage of disease; however, younger age was not an independent risk factor for local recurrence in patients with TNBC [35] . Therefore, age may not be a crucial factor for LRR among patients who presented at a similar clinical stage and all received chemotherapy.…”
Section: Discussionmentioning
confidence: 97%
“…First, selective referral to participating clinics may have limited the applicability of the results derived from hospital-based cohorts (e.g. [7, 35, 40, 4345]) to unselected populations of BRC patients. Second, some population-based studies investigated patient samples with special characteristics (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…At a median follow-up of 74 months, there was no significant difference in local recurrence (LR) or disease-free survival (DFS) between patients <40 and ≥40 years old. The conclusion was ‘Young age at diagnosis is not an independent risk factor for LR or DR in patients with TNBC’ [8]. Furthermore, another report has compared the clinical pathological characteristics of <65 and ≥65 years old TNBC patients.…”
Section: Discussionmentioning
confidence: 99%